Penerapan Model Waterfall Pada Sistem Informasi Layanan Jasa Laundry Berbasis Web - Doni Andriansyah (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - System design is a solution in solving work process problems by utilizing advances in technology and information. Required selection of system development methods that are effective and efficient so that the needs of users can be immediately fulfilled. D'cuci in laundry is a company engaged in laundry services with a wide selection of services such as kiloan (dry washing and ironing, dry and folding, ironing only, and express), laundry and dryclean. In transactions recording has not been computerized thus causing slow work process in obtaining information. It takes the right innovation to solve the problem, one of which is building a website based information system. The system development method used is Waterfall with 5 stages, namely requirement analysis, system design, program code generation, implementation, support and maintenance. The results of this study will produce a website-based laundry service information system that provides ease in conducting the transaction process. Keywords: waterfall model, web design, laundry information system